Design framework of Arabic e-learning games among Non-Arabic speaking learners in a Malaysian University : past, present and future - Sahrir, Muhammad Sabri; Osman, Nurulhuda; Muhammad, Ilyani Syiham; Mohd Noor, Ahmad Yunus (2012)
Educational games have existed among the teaching and learning aids of many disciplines of knowledge. The games vary between traditional non-computer games to computer or digital games. Every mode of educational games has its own history of existence, design and development frameworks, related learning theories, evaluation frameworks, development tools, genres of games, findings and implications in certain fields, learners, and theories. This paper presents a holistic report of a 3 year research project from the year 2008 until 2011 conducted in the Centre for Foundation Studies (CFS), International Islamic University Malaysia (IIUM), in designing, developing and evaluating an online Arabic e-learning games among Non-Arabic speaking pre-university learners. The research process of this project begins with the literature analysis of 3 related theories from Nation [14], Prensky [19] and Mayer [7]. The design and development of this games prototype are modeled based on the methods and approaches of design and development research or DDR [20], or formerly known as developmental research [21]. The results and findings from this project have contributed in adapting the Design and Development Research (DDR) methods in designing educational games[9], presenting a front-end analysis framework in assessing suitable and holistic needs for games design and development[10], suggesting a model of instructional design (ID) for a game-based design[13], formulating design principles[13], portraying a model of mix-method framework for evaluating the games prototype and producing a final product of the games prototype itself[11]. The final product of this e-learning game has also won several awards from research and innovation exhibitions. KEYWORDS: design and development, e-learning games, online Arabic vocabulary games, design principles, formative evaluation, instructional design model (ID).